2020
DOI: 10.1021/acs.biomac.0c00100
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Relationship of Artificial Spider Silk Fibers Produced by Straining Flow Spinning

Abstract: The production of large quantities of artificial spider silk fibers that match the mechanical properties of the native material has turned out to be challenging. Recent advancements in the field make biomimetic spinning approaches an attractive way forward since they allow the spider silk proteins to assemble into the secondary, tertiary, and quaternary structures that are characteristic of the native silk fiber. Straining flow spinning (SFS) is a newly developed and versatile method that allows production und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…In addition, microfluidic spinning has also been applied to successfully fabricate silk hydrogel, micro-fabricated silk films, engineered tubuliform spidroin fiber, silk fibroin-chitosan scaffolds, recombinant spider silk, and CNF-based fibers. [37][38][39][40][41][42][43] These studies further confirmed the important role of the biomimetic spinning channel to regulate the condensed structure of RSF, which is critical to obtain artificial fibers with excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 53%
“…In addition, microfluidic spinning has also been applied to successfully fabricate silk hydrogel, micro-fabricated silk films, engineered tubuliform spidroin fiber, silk fibroin-chitosan scaffolds, recombinant spider silk, and CNF-based fibers. [37][38][39][40][41][42][43] These studies further confirmed the important role of the biomimetic spinning channel to regulate the condensed structure of RSF, which is critical to obtain artificial fibers with excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 53%
“…This meant that if the fibers actually were not circular (but elliptical or dumbbell-shaped) we overestimated the fiber cross-sectional area by a factor of two, and thereby correspondingly underestimated the fiber tensile stress ( Figure S2). Artificial silk fibers with dumbbell-shaped cross-sections have also been observed in NT2RepCT spinning setups which, instead of the pulled glass capillary, employed fluorinated ethylenepropylene tubes with round cross-sections [32], as well as other spinning setups and recombinant spidroins [45]. Notably, in these studies the cross-sectional area was also assumed to be circular when calculating tensile strength.…”
Section: Discussionmentioning
confidence: 94%
“…Spiders are able to keep the spidroins soluble during storage in the glands at an impressive concentration of 30-50% (w/v) [29], and they convert the protein solution into solid fibers using a drop in pH to <5.7 and shear forces [30]. Recently, this high solubility has been achieved for designed recombinant spidroins that were purified from E. coli and kept, in an aqueous buffer, at pH 8.0 [31,32]. Moreover, these recombinant spidroins have been spun into continuous fibers in biomimetic spinning setups where the fibers were formed by extrusion of a highly concentrated protein solution into a collection bath (pH 5.0 aqueous buffer) [31][32][33] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of recombinant silk proteins by cloning the gene expressing the silk fibroin in a host organism [49][50][51]. This approach can be a good answer to provide enough silk biomaterial with tailored properties for clinical usage.…”
mentioning
confidence: 99%